Analisys of Shallot Price Transmission in North Sumatera - Faiz Ahmad Sibuea; Mhd.Buhari Sibuea; Fitriani, Fitriani (Cita konsultindo, 2025)
The short-term dynamics of shallot prices at the producer level generally have the same pattern as the dynamics of shallot prices at the wholesale and retail levels because the partnership faced by producer farmers is a derivative of demand at the retail level.The purpose of this study is to analyze the transmission of North Sumatra shallot prices formed at the producer, wholesale and retail levels and analyze the movement of shallot prices in the future period. This study uses price panel data at the producer, wholesale and retail levels for January - December from 2017 - 2024. The price data is obtained from the Central Bureau of Statistics and the Ministry of Trade. The research methods used are ECM (Error Correction Model) and ARIMA (Auto Regressive Integrated Moving Avarange) models in analyzing price transmission and price movements of shallots in North Sumatra. The results show that price transmission between producers, wholesalers and retailers takes place asymmetrically in the short term and long-term asymmetry. Meanwhile, price transmission between producers and wholesalers takes place symmetrically in both the short and long term. In addition, price forecasting at the producer and retail levels shows relatively stable prices while at the retail level shows relatively declining prices.